Distributed simulation of fully coupled hydrological-hydrodynamic model for predicting rainfall-induced runoff/flood in small watersheds - Yulong Zhu; Yu Gao; Bonan Wang; Binh T. Nguyen; Yafen Zhang; Baolin Xue (Journal of Hydrology: Regional Studies)
Study Region: Two regions in Japan: the Nissho Pass watershed and the Lake Kusaki watershed, which covers an area of 0.1365 km2 and 254 km2 respectively. Study Focus: Extreme rainfall leads to frequent flash flood events. At present, the distributed hydrological model and the two-dimensional hydrodynamic model that can realize distributed runoff simulation have some restrictive factors such as low computational efficiency and poor computational stability. Therefore, this study focuses on developing the fully coupled hydrological-hydrodynamic model, the Distributed Runoff Model (DRM), from distributed computing of simple geometric models to complex terrains in real watersheds. New Hydrological Insights for the Region: Our findings reveal the distributed computing capabilities of DRM model in a small watersheds, which shows potential application values in flood forecasting and real-time hydrological simulations. The performance of DRM was compared with three other models: the iterative cross-coupling model, the shallow water equation model, and the integrated watershed model. Results show that under complex topography and heterogeneous rainfall conditions, the DRM model provides more efficient predictions of distributed water depths and flow velocities compared to the other models. The effectiveness of the DRM model was further validated using measurement data from the Lake Kusaki watershed, confirming its applicability for both small and large-scale watershed simulations.